Features of the organization of medical and psychological assistance in the situation of perinatal losses (literature review) - Astakhov, V.M.; Batsylyeva , O.V.; Puz , I.V.; Shudrikova, N.V. (Medicni Perspektivi, 2022)
The article reveals the organizational features of medical and psychological assistance in cases of perinatal losses in modern conditions. The paper presents the peculiarities of perinatal loss, psychological condition of women’s health during the onset of subsequent pregnancy as well as experiences of the women who have lost a child at different stages of pregnancy. The article notes that the majority of pregnant women with a history of perinatal loss are in a state of chronic stress, which can lead to the emergence and development of various medical and psychological complications. The peculiarities of the experience of grief in the situation of perinatal loss, as a serious mental trauma for the woman's psyche were analyzed. It has been substantiated that the experience of perinatal loss is a non-normative crisis in marital relations, and the process of providing psychological assistance should be directed not only to the woman, but also to the married couple as a whole, which will reduce the risk of rupture of relations, promote their harmonization, which can be considered as an effective resource for a constructive experience of the situation of loss. The main tasks of psychologists and medical staff during the organization of medical and psychological assistance for women and married couples experiencing perinatal loss are also revealed. It is crucial to comprehend the feelings women experience in such cases, which makes medical and psychological care more effective in the process of working with those who are through child loss or have had such an experience previously. The conclusion notes the priority of organizing and providing comprehensive medical and psychological assistance not only to women, but also to married couples in a situation of perinatal loss; the need for special training both for medical psychologists, obstetricians and gynecologists to provide complex assistance to women experiencing perinatal losses.